The Influence of Gojek Food on Increasing Seblak Jeletet Sales - Meiriza, Mica Siar; Sihombing, Lidya Vanya F; Manihuruk, Sarah Desnita; Pakpahan, Gebatania; Sirait, Kevin Daniel (CV. Rayyan Dwi Bharata, 2025)
The development of technology and digitalization has brought significant changes to the culinary industry, particularly in food ordering and delivery systems. This study aims to analyze the impact of online ordering platforms, specifically GoFood, on increasing the sales of Seblak Jeletet Medan. The research method used is descriptive with a quantitative approach, involving interviews with business owners and an analysis of sales data before and after using GoFood. The results show that utilizing GoFood has had a positive impact on business growth, with an increase in the number of customers and daily revenue from IDR 200,000 to IDR 1,500,000–IDR 2,000,000. Additionally, the use of digital technology has improved operational efficiency and customer service quality. Digital marketing strategies through social media and GoFood promotions have proven effective in introducing products to a broader market. Therefore, culinary entrepreneurs are advised to leverage digital platforms to enhance their competitiveness and business growth.